Intergenerational Support and Subjective Wellbeing of the Elderly in Mainland China: The Role of Perceived Health - Na Li; Mang He (SAGE Open, 2023)
The purpose was to examine the relationship between intergenerational support, perceived health and subjective wellbeing (SWB) of the elderly’ s in China, and what role perceived health played in this study. Based on data from Chinese General Social Survey (CGSS) in 2017 ( N  = 1,373), regression analysis was employed to test the mediation effects by software STATA17.0 and Macro PROCESS3.50. The regression results showed that intergenerational support including intergenerational support received and provided had a positive relationship with the elderly’s SWB. And perceived health was positively related to the elderly’s SWB in all models. Providing intergenerational support had a positive impact on the perceived health of elders, but receiving intergenerational support cannot significantly influence it. And the mediating role of perceived health was played in the relationship between the providing intergenerational support and the elderly’s SWB, rather than between the receiving intergenerational support and the elderly’s SWB. Although some limitations were there, the findings contributed to addressing theoretical gaps and giving references for the improvement of policies. Attention should be paid to the effect of intergenerational support on the elderly’s SWB.